Effect of Different Filters on Growth and Survival of Cachama (Colossoma macropomum) in the Recirculation System - Fauzan, Nuhaya Rafi; Putra, Iskandar; Mulyadi, Mulyadi (Jurnal Perikanan dan Kelautan, 2024)
The recirculation system, in principle, is the reuse of water that has been removed from cultivation activities. Cachama (Colossoma macropomum) is a relatively high economic value fishery commodity. This study aimed to obtain the best filter dose for water quality on the survival of cachama. The experimental method used a completely randomized design with six permitted treatments and three replications. The treatment used was P0 (without filter) with P1 (100% charcoal filter), P2 (100% zeolite filter), P3 (50% charcoal and 50% zeolite filter), P4 (25% charcoal and 75% zeolite filter), and P5 (75% charcoal and 25% zeolite filter) the fish kept for 50 days. The results of this study showed that the best treatment was P4 (25% charcoal and 75% zeolite filter), which resulted in a recent weight growth of 6.12 g, static length growth of 4.86 cm, growth rate specific growth of 2.08%, survival of 100%, and food conversion ratio of 1.95. Providing 25% charcoal and 75% zeolite filters affects water quality, growth, and survival rate.